THE APPLICATION OF PROJECT-BASED LEARNING IN SPEAKING CLASS AT THE ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Armas, Muh. Fakhrul; Aeni, Nur; Radhiyani, Fitri (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aimed to describe the application of project-based learning in the speaking class of second-year English language education students, at the State University of Makassar. This study used an exploratory qualitative method. The data of this research were collected through observation, interview, and documentation. The subjects of this study were an English lecturer who teaches in the second-year and the second-year English language education students that consisted of two classes. The result of data analysis found that (1) the application of project-based learning in second-year English language education students has been implemented very well by the lecturer and the students (2) the application of project-based learning in speaking classes for the second-year produces research projects that are presented at the end of the semester using posters (3) constraints encountered in applying project-based learning in speaking classes are students are not used to working in teamwork to work on projects with research output, students have difficulty compiling research instruments, students have difficulty finding respondents, and there are still students who are not actively involved in class (4) the student’s speaking skills and students’ learning motivation have increased after the application of the project-based learning method in the extensive speaking class.